Implementing DDL In English Learning Application for University Students In Indonesia: Student’s Prespective - Zakiyah, Fitriyatuz; Eka Susylowati; Rohmah, Nisaur (International Journal of English and Applied Linguistics (IJEAL), 2026)
This research aimed to analyze the appropriate design for implementing the DDL approach on a web-based English learning platform and students' perspectives on using the DDL to enhance students understanding on English grammar. The post-test and pre-test were employed to measure DDL effectiveness in improving students understanding of English grammar. The 5-point Likert questionnaire was also used to know students’ prespective of its approach. The data was then analyzed quantitatively. The results showed that the students generally have positive experience of exploring DDL instruction in the web. It also supports independent learning, promoting engagement, curiosity, and self-discovery in the learning process. However, several challenges limit its positive impacts.